Paternal variations in fertilization and embryonic development - DATT, MAHESH; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2014)
Four males were used to study the paternal variations in the fertilization, cleavage and development of embryos in vivo. The paternal variations among 4 males were recorded in fertilization and embryonic development from 1-cell stage to blastocyst stage of embryos. The development rates from one to two cell, two to four cell, four to eight cell and morula to blastocyst were 80.90, 50.90, 10.09,7.27 and 6.36%, respectively, for male number. 1; 77.28, 56.61,34.91, 18.98 and 6.77%, respectively, for male number -2; 61.53,43.58, 29.05,16.23 and 5.12 %, respectively, for male number-3; and 71.6,46.13,31.08,20.91 and 8.30, respectively, for male number-4. Among four males used, male number-4 was found the best. The results showed that variations in fertilization and subsequent embryonic development In vitro are related to individual males and hence selection of males employed in the embryo production is an important factor and to be taken into consideration to improve the yield.